Impact of selected Asean countries' price policy on the Malaysian rice industry - Daniel, Mirimo (2015)
The Association of South East Asia Nations (ASEAN) regional integration framework embodied in the Vision 2020 is an ambitious program which is encompassing the socio-political and economic arena of the ten country members. The ASEAN Free Trade Area (AFTA) is the arm by which the ASEAN region is achieving economic integration through the elimination of tariff and non-tariff barriers between countries members. The Common Effective Preferential Tariff (CEPT) Scheme is the main mechanism to move ASEAN towards the direction of the AFTA. The ASEAN Economic Community (AEC) shall be the goal of regional economic integration by 2015. Rice is a staple food in the Asian region, a key indicator of national food security and a main source of income for millions of farmers. All these features have drawn the attention of their policy makers to intervene for sometimes at a pure economic basis, sometimes for both economic and socio-political motivations. These governments direct and indirect interventions in the agricultural sector in general and in the rice sector in particular affected the structure of rice crop production, consumption and trade in not only their respective domestic markets but as well at the global rice market level. Few words have described the global rice market: a thin (almost 8% of world rice productions are traded), fragmented in rice type and quality and a geographic concentration of production (over 90% of rice are produced and consumed in Asia). In Malaysia, rice import is mainly performed within ASEAN region, with Vietnam and Thailand. Currently there is an import duty for rice imports at 20 percent under the Common Effective Preferential Tariff Agreement (CEPT) of AFTA and 40 percent under the Agreement on Agriculture (AoA) of the WTO. Actually there's a sole importer in the country, Padiberas National Berhad (BERNAS), a private entity with the privilege from the government to import rice at duty free rates, but also vested with social obligations on behalf of the Government on the rice industry. Therefore the current policy is an import quota of roughly 35% of domestic rice consumption imposed to the sole rice importer BERNAS.Rice policies in Thailand have always been geared toward domestic production and improving production for trade. Since 2001, the Thai government introduced the Paddy Pledging Program which has been in use on and off since the introduction. The objective of the rice price pledging scheme was to provide a loan at low interest rate to farmers who needed cash in the early harvesting season so that the farmers can keep their products from selling at low price and delay sales until prices rise later. The government has been storing the purchased rice and selling the stock itself at any time. The price support helped farmers increase their income but it worsened the trade competitiveness of Thai rice. Present rice policies in Vietnam are a balance between maintaining domestic food security and promoting rice exports. Government intervention is limited in the domestic market and a majority of rice exports in the country are made through state-owned trading enterprises (50% share), particularly by the Vietnam Food Association (VFA). VFA buys rice from farmers to keep the domestic price of rice stable, maintains rice export registration requirements and the Minimum Export Price (MEP) based on the Government regulation on rice exports, in order to regulate the flow and prices of rice exports. Both the rice pledging program in Thailand and the floor rice export price in Vietnam are price supportive program which only differ in their mechanisms. The first is intended to famers, to increase their income, thus the farmers' paddy price and subsequently the export price; the later is intended to rice exporters to assure a minimum profit, thus rice farmers’ income. The general objective of this study was to assess the impact of selected ASEAN countries' price policy on Malaysia rice industry, with these following specific objectives of developing a system dynamics model for the Malaysia rice industry incorporating the ASEAN rice industry variables, to simulate the impact of change in policy instruments of ASEAN rice policy namely the Vietnam rice floor export price and the on and off Thailand rice pledging program on Malaysia rice industry, at last to provide rice market foresights and policy recommendations to Malaysia rice industry. The system dynamics methodology was the mean by which this study intended to learn and to understand the Malaysia rice industry variables relationship with the ASEAN rice industry variables (Thailand and Vietnam rice export quantities and prices). A causal loop diagram was first developed, then it was converted in a stock a flow diagram to perform some computer simulation (with the help of Vensim software) based on three (3) scenarios including the base line scenario which was drawn based on the World Bank commodity prices forecast until 2025, the first scenarios were concerned with an increasing of export prices of Vietnam and Thailand as the results of removing their policies, an increase of 20 and 40 percent from the base line projection were specifically designed , the second scenarios were looking at downing export prices trend of 10 and 30 percent from the base line scenario.Simulation results from export price scenarios indicated that an increase compared to their base line projections of export prices will decrease the Malaysia rice selfsufficiency level, while the inverse, a decrease of export prices compared to their base line levels will increase the rice self-sufficiency level. All these variations of rice self-sufficiency levels were than one (1) percent.